Review Desain Struktur Atas Jembatan Berdasarkan Kapasitas Struktur terhadap Beban Rencana pada Proyek Revitalisasi Saluran Sungai Asam, Kota Jambi - M.Agustian Harpani; M. Nuklirullah; Diah Khairinnisa (International Forum of Researchers and Lecturers, 2026)
The increasing demand for infrastructure necessitates the construction of reliable bridges with long service lives to ensure smooth mobility. This research focuses on the Griya Lingga Permai Bridge over the Asam River in Jambi City, which is scheduled for widening as part of the Asam River Revitalization program aimed at flood mitigation. Although the project faces delays due to land acquisition constraints, this postponement is leveraged as a strategic opportunity to conduct a design review of the planned bridge superstructure.The bridge is designed using a reinforced concrete